Women's reproductive health in India - Ramasubban, Radhika; Jejeebhoy, Shireen J.; Centre for Social and Technological Change (Mumbai, India) (Jaipur : Rawat Publications, 2000)
Contributed articles.
Adolescent sexual and reproductive behaviour : a review of the evidence from India / Shireen J. Jejeebhoy -- Research on sexuality and sexual behaviour in India, the 1990s / Pertti J. Pelto -- Safe motherhood in India : priorities for social science research / Shireen J. Jejeebhoy -- Abortion research in India : what we know, and what we need to know / Bela Ganatra -- A decade of research on reproductive tract infections and other gynaecological morbidity in India : what we know and what we don't know / Nandini Oomman -- Women's vulnerability : the recent evidence on sexually transmitted infections / Radhika Ramasubban -- From contraceptive targets to informed choice : the Indian experience / Leela Visaria -- Quality of care within the Indian family welfare programme / Gillian Foo and Michael Koenig -- Social policy and reproductive health / Bhanwar Rishyasringa.
"Centre for Social and Technological Change, Mumbai."
Includes bibliographical references and indexes.
Keywords: Women -- Health and hygiene -- India; Reproductive health -- India; Birth control -- Government policy -- India; Sexual behavior surveys -- India